Thesis Preparation Training According to the Template for Physical Education Study Program Students - Jusuf Blegur; Pnatmo Welhelmina Masi; Zuvyati Aryani Tlonaen (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The study program has created a template for a thesis preparation to facilitate and assist students in compiling their thesis. The problem is that the study program still encounters numerous proposal and thesis documents that do not match the template distributed. Therefore, it is necessary to conduct training for students in compiling their thesis following the template. The methods used to carry out this training were lectures, exercises, mentoring, simulations, and evaluations. The material provided included the preparation of a thesis following the physical education study program template, tips on finding credible references for the final project, and technically making citations and compiling the APA model reference by involving 52 students who are preparing their final project, both proposals and theses (only 25 participants whose thesis documents were evaluated). The result showed that students' knowledge and skills in compiling their thesis following the template was improved. Although successful in giving an impact, study programs, course lecturers, supervisors, and examiners need to simultaneously pay attention to the thesis writing as the final project following the template in order to accelerate students to complete their studies.